Ghrelin Ameliorates Diabetic Retinal Injury: Potential Therapeutic Avenues for Diabetic Retinopathy - Jie Bai (Hindawi Limited, 2021)
Ghrelin has anti-inflammatory, antioxidant, and antiapoptotic effects, and it may be beneficial for the treatment of many ophthalmic diseases, such as cataract, uveitis, and glaucoma. Our previous work proved that ghrelin pretreatment reduced the apoptosis of lens epithelial cells induced by hydrogen peroxide, reduced the accumulation of reactive oxygen species (ROS), and effectively maintained the transparency of lens tissue. However, no study has yet investigated the effect of ghrelin on retina. In this study, we conducted in vitro and in vivo experiments to explore the effect of ghrelin on high-glucose- (HG-) induced ARPE-19 cell damage and diabetic retinopathy in streptozotocin-induced diabetic rats. ARPE-19 cells were incubated in a normal or an HG (30 mM glucose) medium with or without ghrelin. Cell viability was measured by 3-(4, 5-dimethylthiazol-3-yl)-2,5-diphenyl tetrazolium bromide assay, and apoptosis was detected by the Hoechst–PI staining assay. Intracellular reactive oxygen species (ROS) production levels within cells were measured using 2′,7′-dichlorofluorescein diacetate staining, and the contents of superoxide dismutase and malondialdehyde were measured using relevant detection kits. The expression levels of IL-1β and IL-18 were measured using an enzyme-linked immunosorbent assay, and those of NLRP3, IL-1β, and IL-18 were measured using Western blotting. The rat diabetes models were induced using a single intraperitoneal injection of streptozotocin (80 mg/kg). The morphological and histopathological changes in the retinal tissues were examined. The results indicated that ghrelin reduced ROS generation, inhibited cell apoptosis and the activation of NLRP3 inflammasome, inhibited the apoptosis of retinal cells in diabetic rats, and protected the retina against HG-induced dysfunction. In conclusion, ghrelin may play a role in the treatment of ocular diseases involving diabetic retinopathy.